Development of a flipped professional module for ESL primary school teachers / Dalwinder Kaur Jaswant Singh - Dalwinder Kaur, Jaswant Singh (2018)
This study introduces a flipped professional development for English as a Second Language (ESL) teachers in an urban district in Malaysia. The shortcomings of the traditional professional development programs have spurred the idea of a flipped professional development. In most cases, traditional professional development programs are mostly held in the form of workshops aim at delivering pedagogical content to teachers; however, they leave no time for the design and implementation of the content. Thus, the idea of flipping the professional development program is to provide ample opportunities for design, development, and implementation of curriculum content via integration of technology. The design of this research, which is adopted from the Design-based Research (DBR) is conducted in seven thorough phases beginning with problem analysis and ending with an evaluation of the effectiveness of the flipped professional development training. The pyramidal framework for the implementation of this research is designed based on the blend of two theories: Bloom’s Revised Taxonomy and Zone of Proximal Teacher Development (ZPTD). The resulting model for training teachers within their Zones of Proximal TeacherDevelopment integrates the social constructivism theory into a model of teacher education. The findings of this study indicates that teachers’ pedagogical content knowledge needs were fulfilled throughout the training; nonetheless, the ESL teachers have shown resistance towards the form of flipped professional development. Teachers are not able to self-direct their own professional development as they are burdened with unending academic and non- academic duties in school, and this provides evidence that such approach is not prevailing in Malaysia. This study, however, synthesizes the features of an effective professional development suggested by Desimone (2011). Desimone (2011) maintained that changes in teacher learning and the effectiveness of the training is spurred by the features of an effective professional development rather than the type of activity. Thus, it can be concurred that this professional development program was successful as the module was developed based on the principles of an effective professional development.